GAMBARAN FUNGSI KOGNITIF PASIEN INFEKSI OTAK DI RSUP PROF. DR. R.D. KANDOU MANADO - Enggune, Chesia Mentari; Pertiwi, Junita Maja; Mawuntu, Arthur H.P. (JKK (Jurnal Kedokteran Klinik), 2018)
AbstractIntroduction: Brain infection can cause various sequels including impaired cognitive function. However, the prevalence and characteristics of impaired cognitive function among brain infection patients in R.D. Kandou Hospital Manado remained not completely recognized. This study aims to determine the prevalence of impaired cognitive function and its characteristics in patients who have been diagnosed as brain infection. Methods: This was a cross-sectional study conducted in R.D. Kandou Hospital from October to December 2017. Patients previously diagnosed as brain infection, aged 17 to 60 years, and alert were invited to follow this study. The variables studied are age, gender, education level, type of brain infection, and cognitive function. The cognitive function was examined by Montreal Cognitive Assessment Indonesian version (Ina-MoCA) and International HIV Dementia Scale (IHDS). Results: We found 15 eligible subjects. Eighteen percent of them were male and the average age is 36.0 (±2.00) year old. Ina-MoCA examination found impaired cognitive function in 73.3% subjects and IHDS in all subjects. The two most frequently found impaired functions were delayed memory and psychomotor speed. Conclusion: Most brain infection patients will have impaired cognitive function and physicians should evaluate cognitive function in patients previously diagnosed as brain infection.Keywords: Cognitive function, brain infection, Ina-MoCA, IHDS, Manado. AbstrakPendahuluan: Infeksi otak menyebabkan berbagai sekuele termasuk gangguan fungsi kognitif. Meskipun demikian, prevalensi dan karakteristik gangguan fungsi kognitif pada pasien-pasien infeksi otak di Rumah Sakit R.D. Kandou Manado (RS RDK) masih belum sepenuhnya diketahui. Penelitian ini bertujuan mengetahui prevalensi gangguan fungsi kognitif dan karakteristiknya pada pasien-pasien yang sebelumnya terdiagnosis infeksi otak. Metode: Ini adalah penelitian potong lintang di RS RDK pada bulan Oktober-Desember 2017. Pasien yang sebelumnya terdiagnosis infeksi otak, berusia 17-60 tahun, dan sadar diajak mengikuti penelitian ini. Variabel-varibel yang diteliti mencakup usia, jenis kelamin, tingkat pendidikan, tipe infeksi otak, dan fungsi kognitif. Fungsi kognitif diperiksa menggunakan Montreal Cognitive Assessment Indonesian version (Ina-MoCA) and International HIV Dementia Scale (IHDS). Hasil: Kami menemukan 15 pasien yang memenuhi kriteria penelitian. Delapan puluh persen adalah laki-laki dan rerata usia adalah 36,0 (±2.,0 ) tahun. Pemeriksaan Ina-MoCA menemukan gangguan fungsi kognitif pada 73,3% subjek dan IHDS pada semua subjek. Dua fungsi yang paling banyak terganggu adalah kecepatan psikomotorik dan memori tunda. Simpulan: Sebagian besar pasien infeksi otak akan mengalami sekuele gangguan fungsi kognitif dan para dokter harus mengevaluasi fungsi kognitif pada pasien yang sebelumnya terdiagnosis infeksi otak.Kata kunci: Fungsi kognitif, infeksi otak, Ina-MoCA, Manado.